Development of Risk Evaluation and Mitigation Systems for Logistics System - Ahmad Rusdiansyah; Della Deswiana Pratama; Muhammad Faisal Ibrahim (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
Logistic activities are significant activities that pose various risks for the company. These risks can affect the company’s performance. To be able to compete in the globalization era, companies need proper risk management. This study aimed to develop Risk Evaluation and Mitigation Systems. We offered four stages: risk identification, risk analysis, risk evaluation, and risk response. A case study was conducted to implement the proposed Risk Evaluation and Mitigation Systems. The results indicated that the proposed Risk Evaluation and Mitigation Systems were proven to be appropriately applied to evaluate company risks and provide mitigation recommendations.